2012
DOI: 10.1111/j.1558-5646.2012.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Preference for Male Courtship Effort Can Drive the Evolution of Male Mate Choice

Abstract: The evolution of male mate choice is constrained by costs of choice in species with a male‐biased operational sex ratio (OSR). Previous theoretical studies have shown that significant benefits of male choice are required, for example, by mating with more fecund females, in order for these costs to be offset and a male preference to spread. In a series of population genetic models we show the novel effect that male mating preference, expressed as a bias in courtship, can spread when females prefer, and thus are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 85 publications
(151 reference statements)
3
51
2
Order By: Relevance
“…It is interesting that the very tendency of females to select males by courtship effort (well documented gryllids [51-54]) might lead to the evolution of male choosiness even in species where males do not invest in offspring. South et al [10] modeled a system in which male choosiness evolved when females preferred males that courted with added intensity. Males that invested a larger proportion of their total courtship effort towards preferred females tended to acquire matings, thereby increasing the frequency of male “choosiness” alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that the very tendency of females to select males by courtship effort (well documented gryllids [51-54]) might lead to the evolution of male choosiness even in species where males do not invest in offspring. South et al [10] modeled a system in which male choosiness evolved when females preferred males that courted with added intensity. Males that invested a larger proportion of their total courtship effort towards preferred females tended to acquire matings, thereby increasing the frequency of male “choosiness” alleles.…”
Section: Discussionmentioning
confidence: 99%
“…However, male mate choice has now been described even in species where males do not invest in offspring care [3-6]. Furthermore, it has been theoretically demonstrated that male and mutual mate choice can evolve in a wide range of circumstances [7-9], especially when females are encountered simultaneously (rather than sequentially), when there is variability in female fertility [3] or when females prefer males that court intensively [10]. …”
Section: Introductionmentioning
confidence: 99%
“…A large number of empirical studies have documented male mate choice as being prevalent in many taxa (for reviews, see Amundsen 2000; Bonduriansky 2001; Kraaijeveld et al. 2007; Hooper and Miller 2008), resulting in several theoretical studies about the evolution of male or mutual mate choice having been published during the last decades (e.g., Ihara and Aoki 1999; Kokko and Johnstone 2002; Servedio and Lande 2006; Servedio 2007; Nakahashi 2008; Barry and Kokko 2010; South et al 2012). …”
mentioning
confidence: 99%
“…Significant benefits are required to offset the potential costs of male choice, such as through obtaining greater investment from more fecund females (Servedio and Lande 2006; Servedio 2007; Nakahashi 2008), assortative mating according to female quality (Fawcett and Johnstone 2003; Härdling and Kokko 2005; Venner et al. 2010), and a female preference for males that court them more vigorously (South et al 2012). In such cases, males would make their choice before pairing and copulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation